Freedom and Frustration: Rachel Dolezal and the Meaning of Race. (August 2019) - Osuji, Chinyere
Where ethnoracial boundaries are treated as rigid and real, their consequences are also rigid and real. But if Rachel Dolezal had lived in Brazil, she would have been just another negra frustrada .